2013
DOI: 10.1163/1568539x-00003106
|View full text |Cite
|
Sign up to set email alerts
|

Differential allocation in relation to mate song quality in the Bengalese finch

Abstract: Postmating sexual selection plays an important part in the evolution of secondary sexual characters. Based on differential allocation theory that predicts biased reproductive investment of females depending on the attractiveness of mates, a number of previous studies have shown that egg production is related in various ways to ornamental sexual traits of males, but evidence for behavioral sexual traits is less abundant. In this study we examine such maternal effects in relation to birdsong.Because the Bengales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 82 publications
(98 reference statements)
1
6
0
Order By: Relevance
“…In line with this study, female birds generally invest more in offspring when paired with preferred than with un-preferred males (Horváthová et al, 2012). This is known as the (positive) differential allocation hypothesis (DAH) (Burley, 1986;Ratikainen and Kokko, 2010;Sheldon, 2000) and has been shown for several reproductive variables, such as offspring provisioning (Pryke and Griffith, 2010), androgen deposition in the egg (Gil et al, 1999), egg mass (Cunningham and Russell, 2000;Soma and Okanoya, 2013), or clutch size (Loyau et al, 2007). The result showed that offspring quality may be better as has been shown by positive correlations between paternal attractiveness and offspring quality (Petrie and Williams, 1993;Sheldon et al, 1997).…”
Section: Introductionsupporting
confidence: 73%
“…In line with this study, female birds generally invest more in offspring when paired with preferred than with un-preferred males (Horváthová et al, 2012). This is known as the (positive) differential allocation hypothesis (DAH) (Burley, 1986;Ratikainen and Kokko, 2010;Sheldon, 2000) and has been shown for several reproductive variables, such as offspring provisioning (Pryke and Griffith, 2010), androgen deposition in the egg (Gil et al, 1999), egg mass (Cunningham and Russell, 2000;Soma and Okanoya, 2013), or clutch size (Loyau et al, 2007). The result showed that offspring quality may be better as has been shown by positive correlations between paternal attractiveness and offspring quality (Petrie and Williams, 1993;Sheldon et al, 1997).…”
Section: Introductionsupporting
confidence: 73%
“…We have categorized these hypotheses as follows: Parental investment is lower in noisy areas . Because females in some species alter parental investment according to the attractiveness of a male's song (Garcia‐Fernandez et al, 2013; Soma and Okanoya, ; Krištofík et al, ), song changes made to overcome masking noise may be considered less attractive and therefore affect female reproductive allocation (Habib et al, ; Halfwerk and Slabbekoorn, ), resulting in lower reproductive success in urban areas. Noisy territories are lower quality / are held by lower quality males . Both territory quality and male quality can affect reproductive success, and are often correlated (reviewed in Andersson, ).…”
mentioning
confidence: 99%
“…It is possible that age‐ related body size change is the underlying cause, and it would be of value for future studies to test if aging under better nutritional conditions leads to a higher rate of increment in song length compared with aging under mal‐nutritional conditions. Although we do not have a full understanding of female preference in estrildid finches (but see Okanoya , Riebel ), in the zebra finch, females are reported to prefer longer song duration, which is both within the normal range (Vyas et al ) and beyond the male zebra finch's capacity (Neubauer ), and in the Bengalese finch, preference for longer songs has also been reported (Soma and Okanoya ). Presumably this preference is because longer songs guarantee better mates in terms of physical condition and age.…”
Section: Discussionmentioning
confidence: 94%